Graha Sastra Di Pekanbaru Dengan Pendekatan Arsitektur Postmodern - Neni Meilani Damanik; Ratna Amanati; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Literature as an art and culture can be used to convey many forms of messages like moral, religion and cultural values that can affect the mindset of society. As time goes by, the art of literature started neglected. This is cause a certain anxiety of the existence of literary art in the future. Related to this issue, Pekanbaru needs The Graha Sastra facilities which can serve as a space and a media appreciation of the literary art. To achieve this goal, Graha Sastra was designed with facilities that can support the literary arts development activities such as education, production and recreation facilities.